Polylactic acid/thermoplastic tapioca starch blend incorporated with selected essential oils for active food packaging - Ajiya, Adamu Dahiru (2019)
The environmental effect of petroleum-based polymers and the activity of food spoilage microorganisms made researchers work on alternative bioactive packaging materials. This work aimed at producing sustainable thermoplastic tapioca starch (TPTS) and its polylactic acid (PLA) blend with introduction of antimicrobial (AM) activity via incorporation of lemongrass (LG), lemon balm (LB) and pandan (PA) essential oils (EOs) on the films. The plasticising effect of glycerol and water and compatibilising effect of vinegar loadings on the properties of TPTS were tested. So also the impact of TPTS loading on the PLA/TPTS blend properties. Furthermore, the AM activity of TPTS incorporated with the EOs on E. coli, B. cereus and S. marcescens was evaluated by inhibitory zone; and packaging effect of PLA/TPTS films coated with the EOs on death rate of microorganisms inoculated on Bahulu cake was investigated. The TPTS was formed by tape casting method, while PLA/TPTS film by hot pressing. The results indicated an increase in crystallinity and elongation at break with increase in plasticiser loading in TPTS and percentage TPTS loading in PLA/TPTS blend; both were accompanied by a decrease in Tg and tensile strength. Continuous surface morphology was seen at high plasticiser loading in TPTS, while high TPTS loading manifested a phase separation in PLA/TPTS blend. The results show that 125 C processing temperature, 15 wt% glycerol, 45 wt% water and 3.5 wt% vinegar loading were optimum parameters for TPTS production. Whereas, 185C processing temperature and 25 wt% TPTS loading are optimum parameters for PLA/TPTS blend production. Citral was found as the common active compound among the EOs. LG and LB were active against all the tested microorganisms, while PA was very mild at higher concentration. For active TPTS and PLA/TPTS films activity, E. coli: LB˃LG˃PA; B. cereus: LG˃LB˃PA; S. marcescens: LB˃LG˃PA. The TPTS and PLA/TPTS active films produced have shown improved properties for food packaging and effective AM activity against the selected microorganisms.